If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(8y + 2) + -1(-7y + -5) = -1 Reorder the terms: -1(2 + 8y) + -1(-7y + -5) = -1 (2 * -1 + 8y * -1) + -1(-7y + -5) = -1 (-2 + -8y) + -1(-7y + -5) = -1 Reorder the terms: -2 + -8y + -1(-5 + -7y) = -1 -2 + -8y + (-5 * -1 + -7y * -1) = -1 -2 + -8y + (5 + 7y) = -1 Reorder the terms: -2 + 5 + -8y + 7y = -1 Combine like terms: -2 + 5 = 3 3 + -8y + 7y = -1 Combine like terms: -8y + 7y = -1y 3 + -1y = -1 Solving 3 + -1y = -1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = -1 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = -1 + -3 -1y = -1 + -3 Combine like terms: -1 + -3 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4
| B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 | | (23y^2+4y^3-12)-(11y^3-8y^2+y)= | | 3.1q-2.2-5.3q=-3.2q-1.2 | | 9+x^2=0 | | 39=x+5 | | 2.2q-4.7-4.5q=3.3q-3.7 | | 39=x+5*3 | | (2z+5c-3a)-(6a+2c-4z)= | | -3(x+4)+13=-2x-11 | | (y-z-b)-(b+y+z)= | | (7262x)+(1.26a)-(2844x-8.23a)= | | 2x^5+7x^4-10x^3-53x^2-28x+28= | | (72.62x)+(1.26a)-(2844x-8.23a)= | | 8(2x-9)=2(8x+6) | | 3x^3=32 | | 9+11z-3=5z+69-3z | | -3(x-1)-7=4x-11 | | 18+3y=9y | | (24.2x)+(8.25)+(83.6x-2.92)= | | 4x=28-0.25(4-16x) | | 5n-6(n+2)=14 |